+0  
 
0
308
1
avatar

1+2log(x,3)=log(28,3) + log(x,3)- log(9,3)

Guest Feb 18, 2017
 #1
avatar+92805 
0

1+2log(x,3)=log(28,3) + log(x,3)- log(9,3)

 

\(1+2log_3x=log_328 + log_3x- log_39\\ 1+2log_3x=log_328 + log_3x- 2\\ log_3 x=-3+log_3 28\\ x=3^{-3+log_3 28 }\\\)

 

3^(-3+(log(28)/log(3))) = 1.037037037037037

 

x=1.037037037037037

Melody  Feb 18, 2017

3 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.